PLATINUM RECOVERY FROM USED AUTO CATALYSTS: DISSOLUTION AND PRECIPITATION STUDIES - KASZA, Angela M.; KATONA, Gabriel; DAN, Monica; VOICA, Cezara; GRAD, Oana; MIHEȚ, Maria; DEZSO, Tibor; NAGY, Ruben; BOTS, Tihamer; LAZǍR, Mihaela Diana (Studia Universitatis Babeș-Bolyai Ambientum, 2021)
Noble metals are used in a plethora of applications, from electronic and communication equipments, to aerospacial engines, mobile phones and catalytic convertors. Currently, there is a continuous interest in the recovery of noble metals from waste, as their natural reserves are limited. Herein, the paper presents studies on the recovery of platinum from spent automotive catalysts. The process involves two steps - dissolving of platinum, followed by its precipitation into a hexacloroplatinum complex. The optimum reaction conditions for dissolving Pt from the spent automotive catalyst use a mixture of H2O2 + HCl (1:5.5 molar ratio) at 30°C, for 8 h. For the full recovery of platinum from the solution, the volumetric ratio of 4:1 between the platinum solution and the precipitating ammonium chloride solution is optimum. In addition, studies regarding the precipitation time and temperature have also been performed. All the obtained precipitates were analyzed by X-ray powder diffraction and showed the structure of the hexachloroplatinic (NH4)2[PtCl6] complex, with high purity. Upscaling of the processes for technological transfer show promising results in the recovery of platinum from spent automotive catalysts.